Hemorrhagic Stroke in Infants and Children - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1993)
Medical and autopsy records, and brain imaging studies of 178 children with possible stroke within the Greater Cincinnati metropolitan area child population of almost 300,000 during 1988 and 1989 were reviewed in the Departments of Neurology and Neuroradiology, University of Cincinnati and Children's Hospital Medical Centers.